Climate Change: The Urgent Need for Global Health Strategies to Counter Adverse Impacts on Human Health - Macnab, Andrew John (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2025)
The environmental consequences of climate change have become a global health emergency. Reports and reviews continue to document multiple health impacts from increasing temperatures, rising sea levels and more frequent extreme weather events like severe drought, flooding and wildfires. The consequences of global warming on human health include heat-related morbidity and mortality, an increase in vector borne and infectious diseases, greater severity of respiratory diseases, adverse nutritional effects from food insecurity, higher rates of injury and multiple effects from financial, educational, social and psychological stressors. The extent to which climate change is impacting human health and lives is such that action by the public health community is urgently required to provide public education and define effective intervention, prevention and treatment strategies. Only in this way can the initiatives and policies be generated that are required to inform and engage everyone in society, and make people aware that action is needed to counter the dangers to health posed by climate change. Published: 05 February 2025.